[tex]y-5= \frac{-13}{6(x-1)} [/tex]
Refine [tex]y-5 = - \frac{13}{6(x-1)} [/tex]
Expand [tex]- \frac{13}{6(x-1)} = - \frac{13}{6x-6} [/tex]
Multiply both sides by 6 x - 6
(6x-6)y -(6x-6)5 = - (6x-6)[tex] \frac{13}{6x-6} [/tex]
Refine:
(6x-6)y - (6x-6)5 = 13
6xy - 6y - 30 x + 30 = - 13
6xy - 6y -30x + 30 + 30 x = -13+30x
6xy - 6y + 30 = -13+30x
6xy - 6y +30-30 = - 13 + 30 x -30
6xy - 6y = 30 x - 43
take out y :
y(6x-6) = 30 x - 43
Divide both sides by 6x - 6 :
[tex] \frac{y(6x-6)}{6x-6} = \frac{30x-43}{6x-6} [/tex]
[tex]y = \frac{30x-43}{6x-6} [/tex]
hope this helps!